Synthesis and Characterization of Nickel Ferrite (NiFe2O4) Nanoparticles Prepared by Sol- Gel Method. (2015) - Sen, Ravindra; Jain, Pranat; Patidar, Ravi; Srivastava, Sanjay; Rana, R.S.; Gupta, Nitish
Abstract: Nickel ferrite nanoparticles were syntheiszed by sol-gel method using urea as a fuel. The nanoparticles were characterized by XRD, SEM, TGA, FTIR and UV–visible techniques. TGA showed that the gel decomposed around 230 ∘C followed by crystallization. XRD revealed the formation of spinel structure with space group of Fd3m. Scherrer and Williamson-Hall method is applied to determine crystal size and strain present in sample. FTIR showed fundamental absorption bands related to octahedral and tetrahedral sites, in the range 400–600 cm -1 . SEM showed agglomerated flakes having void and pores on the surface. UV–vis indicated the bandgap of sample is 5.5 eV .